2017
DOI: 10.1097/j.pain.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Rab7—a novel redox target that modulates inflammatory pain processing

Abstract: Chronic pain is accompanied by production of reactive oxygen species (ROS) in various cells that are important for nociceptive processing. Recent data indicate that ROS can trigger specific redox-dependent signaling processes, but the molecular targets of ROS signaling in the nociceptive system remain largely elusive. Here, we performed a proteome screen for pain-dependent redox regulation using an OxICAT approach, thereby identifying the small GTPase Rab7 as a redox-modified target during inflammatory pain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…NRF2 and STAT3 are key regulators of cellular antioxidant and immune responses. Our results suggested that rab7 may be essential for maintaining the antioxidant and immune balance, as supported by other studies [ 46 , 47 , 48 , 49 , 50 ]. Most importantly, we predicted multiple FOXO3 transcription factor binding sites in the rab7 promoter region ( Figure 2 ), confirming our initial hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…NRF2 and STAT3 are key regulators of cellular antioxidant and immune responses. Our results suggested that rab7 may be essential for maintaining the antioxidant and immune balance, as supported by other studies [ 46 , 47 , 48 , 49 , 50 ]. Most importantly, we predicted multiple FOXO3 transcription factor binding sites in the rab7 promoter region ( Figure 2 ), confirming our initial hypothesis.…”
Section: Discussionsupporting
confidence: 91%
“…Zymosan- and Complete Freund′s Adjuvant (CFA)-induced paw inflammation. Induction of paw inflammation by zymosan and CFA has been described previously [ 6 , 36 ]. Briefly, 15 µL of a zymosan A suspension (5 mg/mL in 0.1 M PBS, pH 7.4; Sigma-Aldrich, Steinheim, Germany) or 20 µL of complete Freund‘s adjuvant (CFA; containing 1 mg/mL heat-killed Mycobacterium tuberculosis in paraffin oil 85% and mannide monooleate 15%; Sigma-Aldrich) was injected into the plantar subcutaneous space of a hind paw [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tissue preparation and immunofluorescence staining were performed as described previously [ 6 , 31 , 36 ]. Shortly, mice were intracardially perfused with 4% paraformaldehyde in PBS (pH 7.4) and the lumbar spinal cord (L4–L5) and dorsal root ganglia (DRGs) (L4–L6) were dissected, post-fixed, and cryoprotected in 20% sucrose overnight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations